2006
DOI: 10.1002/elan.200603525
|View full text |Cite
|
Sign up to set email alerts
|

Renaissance of HF Impedimetry in Application to CE Detection

Abstract: Some results obtained at the above department in the field of contactless conductivity detection (CCD) are reviewed, in the framework of the state-of-the-art of the field. Several detection cells have been designed and tested. It has been shown that the performance of systems with planar and semitubular electrodes is fully comparable with that of common cells with tubular electrodes and that these systems have advantages in simpler construction and a greater operational versatility. Important characteristic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…This is in agreement with the previous observations on the functioning of contactless conductivity cells [28][29][30] from which it follows that the electric current passes through an effective electrode width which is different from the geometric electrode width. The dependence of the cell impedance on the electrode width passes through a minimum and the current flowing through the cell follows this minimum.…”
Section: Response-frequency Dependencesupporting
confidence: 91%
See 1 more Smart Citation
“…This is in agreement with the previous observations on the functioning of contactless conductivity cells [28][29][30] from which it follows that the electric current passes through an effective electrode width which is different from the geometric electrode width. The dependence of the cell impedance on the electrode width passes through a minimum and the current flowing through the cell follows this minimum.…”
Section: Response-frequency Dependencesupporting
confidence: 91%
“…[28,30] that the electrode effective width is a complex function of the test solution conductivity, the signal frequency and the width of the gap between the electrodes. When using the above model, it can also be demonstrated that the electrode effective width also depends on the thickness of the insulator layer between the electrodes and the solution: the effective width increases with increasing insulator thickness.…”
Section: Response-frequency Dependencementioning
confidence: 99%
“…Even a photothermal process has been employed for detection, combined with CCD [95]. Two recent papers deal with the CCD theory [86,96], one paper compares various CCD detectors for determination of small inorganic ions [97] and a few papers review the field [17,18,20,98].…”
Section: Low-and High-frequency Measurement Of Impedancementioning
confidence: 99%
“…Data given in Table 1 are estimated values obtained without preconcentration methods [14,40,58,94,98].…”
Section: Selectivementioning
confidence: 99%
“…Under these conditions, the experimental dependences are better defined, their non-linearity is considerably suppressed and the measurements have become sensitive and reliable. Consequently, there has been rapid progress in the cell design and in extensive application of high-frequency impedimetry, primarily to monitoring of various substances in liquids and to detection of analytes in microfluidic systems, in capillary electrophoresis, flowinjection analysis and liquid chromatography [10][11][12][13]. The most common approach to all these measurements is the monitoring of the resistance component of the impedance, which depends on the test solution conductivity.…”
Section: Introductionmentioning
confidence: 99%